Negotiating Translators, State, and Local Communities: The Genealogy of Qur'anic Translation in the Jambi Malay Language - Taufik, Ahmad; Nugroho, Bambang Husni (Jurnal Ilmiah Al-Mu'ashirah: Media Kajian Al-Qur'an dan Al-Hadits Multi Perspektif, 2025)
This article explores the ideological negotiations involved in the establishment process of the Al-Qur’an and Terjemahnyo: Bahaso Melayu Jambi (QTBMJ), a Qur’anic translation project supported by the Indonesian Ministry of Religious Affairs. This study investigates how the process of vernacularizing the Qur’an into Jambi Malay reflects the interaction between state ideology, translator agency, and local cultural values. Utilizing Michel Foucault’s framework of power relations combined with a descriptive-analytical method, this study focuses on examining the archival documents, interview reports, and content analysis related to QTBMJ. It was found that the word choice of Qur’anic vocabulary in QTBMJ is not considered a neutral linguistic act but rather a result of negotiation process between religious, political, and social ideologies. Another concern is due to translation choices concerning gender-sensitive terms (e.g., qawwamun, al-nisā’, nafs wahidah) and how these reflect the broader shifts in religious and gender discourse in Indonesia. This article argues that the translation of the Qur’an into a local language is a complex process that involved dynamic interaction between state authority, translator subjectivity, and moral tradition of the local community. This study will contribute to the growing literature on Vernacular Islam, Qur’anic Translation, and The Language of Political Religious in Southeast Asia.